Current insights: a systemic review of therapeutic options for peanut allergy. Issue 3 (11th June 2022) - O'Rourke, Eimear; Tang, Hilary; Chin, Andrew; Long, Andrew; Sindher, Sayantani; Chinthrajah, R. Sharon
Abstract : Purpose of review: With increasing prevalence of peanut allergy (PA) globally and the greater risk of potential reactions occurring due to the leading role of nuts in food products, PA has become a significant public health concern over the past decade, affecting up to 5 million of the US adult population. This review details updates and advances in prevalence, diagnosis, and immunotherapies that have occurred over the past year. Recent findings: Therapeutic and diagnostic advances remain at the forefront of research and have continued to push the food allergy (FA) field forward to provide a promising role in the detection and treatment of PA. The FA field has researched significant advances in peanut immunotherapy, biomarker diagnosis, and quality of life (QoL) improvement. Summary: Given the burden and consequences for individuals with PA, these advances delivered in clinical practice can significantly improve the QoL of individuals with PA and their caregivers. Ongoing studies will continue to investigate long-term outcome measures of desensitisation and effective management plans tailored to the families' needs.